2020
DOI: 10.1186/s12889-020-09202-6
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a hypothetical preventative HIV vaccine among people who use drugs in Vancouver, Canada

Abstract: Background: As research on HIV vaccines continues to advance, studies exploring the feasibility of this intervention are necessary to inform uptake and dissemination strategies with key populations, including people who use drugs (PWUD). Methods: We conducted 25 in-depth qualitative interviews examining HIV vaccine acceptability among PWUD in Vancouver, Canada. Participants were recruited from an ongoing prospective cohort of HIV-negative PWUD. Data were coded using NVivo, and analyzed thematically. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Additionally, PWUD were more likely, compared to non-users, to have refused a vaccine in the past (COVID-19 vaccines among other vaccines). This supports the notion that drug use may be associated with hesitancy of other types of vaccines [ 22 26 ]. Although COVID-19 vaccines were, at the time, provided free-of-charge in the U.S., PWUD were more likely to report, “I don’t want to pay for it” than non-users, suggesting that immunization campaigns advertising vaccines as free regardless of insurance status [ 48 ], may not be reaching or be trusted by PWUD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, PWUD were more likely, compared to non-users, to have refused a vaccine in the past (COVID-19 vaccines among other vaccines). This supports the notion that drug use may be associated with hesitancy of other types of vaccines [ 22 26 ]. Although COVID-19 vaccines were, at the time, provided free-of-charge in the U.S., PWUD were more likely to report, “I don’t want to pay for it” than non-users, suggesting that immunization campaigns advertising vaccines as free regardless of insurance status [ 48 ], may not be reaching or be trusted by PWUD.…”
Section: Discussionsupporting
confidence: 82%
“…Studies investigating people who inject drugs have indeed reported lower COVID-19 vaccination rates in Australia and Baltimore, Maryland in the U.S. [ 18 , 21 ]. Reports of lower flu vaccine [ 22 , 23 ] and hepatitis A and B vaccine uptake [ 24 , 25 ], as well as low willingness for a potential HIV vaccine uptake among PWUD have also been published [ 26 ]. Nevertheless, data regarding COVID-19 vaccine uptake among PWUD in the Southern U.S. is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…77 Misinformation fueled strong skepticism toward the vaccine, which was predominantly framed by distrust in government, pharmaceutical companies in general, and adverse experiences within healthcare systems. 16,18,19,24,26,36,40,41,50,53,55,59,62,64,70,73,80 Participants in both high-and low-incidence populations expressed varying degrees of discomfort and suspicion about the hypothetical vaccine, as they believed that risks or toxicities of an HIV vaccine might not be fully disclosed to the public. Non-Hispanic Black women in a qualitative study conducted in Canada reported that governments and the medical community could not be trusted with the well-being of Black people, 36 and Indigenous Lesbian, Gay, Bisexual, and Transgender (LGBT) communities in another Canadian qualitative study indicated that fear of western "White man's medicine" demotivated their HIV vaccine acceptance.…”
Section: Misinformation and Distrustmentioning
confidence: 99%
“…Participants reported anticipated stigmatization of HIV/ AIDS as a major deterrent to HIV vaccine acceptance, and it was more frequently mentioned in studies of high-incidence populations 21,22,25,26,33,[35][36][37][38][39][40][41]50,53,56,70,71,73,78,80,87 compared with those of low-incidence populations. 51,66 Participants' fear of being labeled and judged by others as living with HIV, having multiple sexual partners, or engaging in risky behaviors increased their hesitancy and reduced acceptance of the HIV vaccine.…”
Section: Hiv Stigmamentioning
confidence: 99%
See 1 more Smart Citation